Feminism in the Short Story Mereka Bilang Saya Monyet by Djenar Maesa Ayu - Irham Thufani Anshori; Amri, Miftachul; Ayu, Hujuala Rika (Journal of Indonesian Literacy and Indigenous Culture, 2025)
This study aims to analyse the representation of feminism in the short story Mereka Bilang Saya Monyet by Djenar Maesa Ayu using a feminist literary criticism approach. A qualitative method with a descriptive-analytical approach is used to identify feminist symbolism, narratives, and themes that describe women’s experiences as well as criticism of patriarchal norms. Data were obtained through literature study and critically analysed using feminist theory to reveal issues of gender injustice, women’s subordination, and resistance to oppression. The results show that this short story represents women’s experiences in patriarchal structures through symbols such as cages, bodies, and knives, which depict sexual violence, social stigma, and the main character’s struggle against patriarchal domination. The emotional and fragmentary narrative reinforces the critique of cultural norms that silence women. The conclusion of this study is that the short story Mereka Bilang Saya Monyet becomes an effective medium of social criticism, highlighting gender inequality and advocating awareness of women’s rights. The contribution of this research lies in the enrichment of feminist studies in Indonesian literature and its implications for interdisciplinary studies between literature, gender and sociology. This research strengthens the position of literature as a tool of cultural resistance and encourages further discussion on social transformation towards gender equality.